Answer:
-6
Step-by-step explanation:
All you have to do is plug in the -3 in the expression so the new expression would be -3(2) so the answer is -6
Answer:
-10
Step-by-step explanation:
45 minutes is half of an hour and 30 minutes
it is none since there is no relation
Answer:
![\large\boxed{(-2z^2-14)-(-12z^2)=10z^2-14}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%28-2z%5E2-14%29-%28-12z%5E2%29%3D10z%5E2-14%7D)
Step-by-step explanation:
![(-2z^2-14)-(-12z^2)=-2z^2-14+12z^2\qquad\text{combine like terms}\\\\=(-2z^2+12z^2)-14=10z^2-14](https://tex.z-dn.net/?f=%28-2z%5E2-14%29-%28-12z%5E2%29%3D-2z%5E2-14%2B12z%5E2%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C%3D%28-2z%5E2%2B12z%5E2%29-14%3D10z%5E2-14)